Characteristics analysis of compact cesium atomic clock with magnetic state selection - Chen, Jiang; Wang, Ji; Guo, Lei; Yang, Jun; Ma, Pei; Huang, Liangyu; Liu, Zhidong (Frontiers in Physics, 2022)
This paper introduces a compact magnetic state-selection cesium atomic clock called LIP Cs-3000 and analyses its characteristics. The test results reveal that the ranges of the line width, peak-to-valley ratio and signal-to-noise ratio of Ramsey pattern are 340 410Hz, 2 13 and 2000 8000 respectively. The corresponding distributions of these parameters are derived by using statistical methods. According to these results, some suggestions are put forward for the further development of the clock. It is also pointed out that the most important factor affecting the accuracy of LIP Cs-3000 atomic clock is the uncertainty of cavity phase shift. In addition, the method to estimate the lifetime of a clock has been proposed. In the end, the paper gives some environmental adaptability designs of the clock, which enable the clock to be used in complex environments.